Analysis of Vehicular and Pedestrian Flow in Metropolitan Area of Lagos (Global Journal of Science Frontier Research, 2018)
The crisis in transport is largely as a result of the growing concentration of population rapid urbanization and economic activities of certain part of the world Attempt to eliminate the traffic functional problem had led to gradual spatial restriction of pedestrian movement This is a result of lack of consideration for pedestrian facilities in the road design and construction Hence pedestrians compete for the use of road designed purely for vehicular use consideration and thereby creating conflicts and accidents on roads most especially within the central business district and other commercial areas In the light of this the research study examined the problems associated with pedestrian and vehicular traffic in an Urban Metropolitan Area Questionnaires were used for data collection from respondents in addition to secondary data extracted from documented information related to the research on causes effect and solution to pedestrian and vehicular traffic conflict on Nigeria roads Finding in this research work revealed that pedestrian and vehicular conflicts in the Urban Metropolitan Area led to traffic jam delay and congestion The conflict was found to be associated with roadside road median and footbridge trading on-street parking of commercial transport operators inadequate traffic and parking facilities Finally recommendations were made for the provision of Parking Facilities Parking Control Effective Traffic Management Pedestrian Traffic Management and Enforcement of Edict by laws and Road Maintenance
Keywords: population; pedestrian and vehiculartraffic; management